1995
DOI: 10.1046/j.1537-2995.1995.351196110892.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐unit and second transfusions of red cells enzymatically converted from group B to group O: report on the end of phase 1 trials

Abstract: ECO RBCs are safe and efficacious when transfused more than once or in multiple-unit volumes to group O or A subjects, and ECO RBCs prepared with recombinant or native enzyme are equivalent in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…1); however, the low pH preference of the human enzyme [pH Ϸ5 (15)] would most likely prevent its use ex vivo on tissues or organs for any extended period of time without significant cell death. To date, the most useful enzyme for cleaving cell surface Gal␣(1,3)Gal has been coffee bean ␣-galactosidase, which works efficiently ex vivo at physiological pH to cleave galactosyl residues and convert group B to group O erythrocytes (26,27). However, because the Gal␣(1,3)Gal epitope is continually resynthesized and replaced, efforts were directed to determine whether ␣-galactosidase could be constitutively expressed in cells, thereby decreasing the amount of cell surface Gal␣(1,3)Gal.…”
Section: Discussionmentioning
confidence: 99%
“…1); however, the low pH preference of the human enzyme [pH Ϸ5 (15)] would most likely prevent its use ex vivo on tissues or organs for any extended period of time without significant cell death. To date, the most useful enzyme for cleaving cell surface Gal␣(1,3)Gal has been coffee bean ␣-galactosidase, which works efficiently ex vivo at physiological pH to cleave galactosyl residues and convert group B to group O erythrocytes (26,27). However, because the Gal␣(1,3)Gal epitope is continually resynthesized and replaced, efforts were directed to determine whether ␣-galactosidase could be constitutively expressed in cells, thereby decreasing the amount of cell surface Gal␣(1,3)Gal.…”
Section: Discussionmentioning
confidence: 99%
“…Specific exoglycosidases have been used to convert blood types B and A to type O. Studies by Lenny et al [241–243] have shown that an exoglycosidase from green coffee bean is able convert blood type B to type O at pH 5.5 by removing the relevant terminal sugar. These RBCs appeared to survive normally in all recipients.…”
Section: Choosing Target Binding Sites On Carrier Rbcsmentioning
confidence: 99%
“…Despite this, coffee-bean-derived enzyme was successfully used to complete phase I (Lenny et al, 1991(Lenny et al, , 1994(Lenny et al, , 1995 and phase II clinical trials in which B-ECO RBCs were shown to be safe and functional, providing RBC survival and recovery values equal to ABO-compatible control transfusions in patients during a randomized cross-over study (Kruskall et al, 2000).…”
Section: The Eco Process and The Enzymesmentioning
confidence: 99%
“…Clinical phase I studies were conducted using B-ECO RBCs given to group A and O healthy volunteers and the initial small infusions were escalated to full single RBC units (Lenny et al, 1991), multiple units and finally repeated transfusions (Lenny et al, 1994(Lenny et al, , 1995. A successful phase II cross-over clinical trial in patients was reported in 2000 (Kruskall et al, 2000).…”
Section: Clinical Experience With Eco Rbcsmentioning
confidence: 99%